The Therapeutic Prospects of Naturally Occurring and Synthetic Indole Alkaloids for Depression and Anxiety Disorders. (16th October 2020) - Munir, Samman; Shahid, Aqsa; Aslam, Bilal; Ashfaq, Usman Ali; Akash, Muhammad Sajid Hamid; Ali, Muhammad Akhtar; Almatroudi, Ahmad; Allemailem, Khaled S.; Rajoka, Muhammad Shahid Riaz; Khurshid, Mohsin
Abstract : Depression and anxiety are the most common disorders among all age groups. Several antidepressant drugs including benzodiazepine, antidepressant tricyclics, azapirone, noradrenaline reuptake inhibitors, serotonin selective reuptake inhibitors, serotonin, noradrenaline reuptake inhibitors, and monoamine oxidase inhibitors have been used to treat these psychiatric disorders. However, these antidepressants are generally synthetic agents and can cause a wide range of side effects. The potential efficacy of plant-derived alkaloids has been reviewed against various neurodegenerative diseases including Alzheimer's disease, Huntington disease, Parkinson's disease, schizophrenia, and epilepsy. However, data correlating the indole alkaloids and antidepressant activity are limited. Natural products, especially plants and the marine environment, are rich sources of potential new drugs. Plants possess a variety of indole alkaloids, and compounds that have an indole moiety are related to serotonin, which is a neurotransmitter that regulates brain function and cognition, which in turn alleviates anxiety, and ensures a good mood and happiness. The present review is a summary of the bioactive compounds from plants and marine sources that contain the indole moiety, which can serve as potent antidepressants. The prospects of naturally occurring as well as synthetic indole alkaloids for the amelioration of anxiety and depression-related disorders, structure-activity relationship, and their therapeutic prospects have been discussed.